2012
DOI: 10.1017/s003329171200164x
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, character and serotonin activity in the human brain: a positron emission tomography study based on a general population cohort

Abstract: Tuominen, L.; Salo, J.; Hirvonen, J.; Någren, K.; Laine, P.; Melartin, T.; Isometsä, E.; Viikari, J.; Cloninger, C. R.; Raitakari, O.; Hietala, J.; and Keltikangas-Järvinen, L., ,"Temperament, character and serotonin activity in the human brain: A positron emission tomography study based on a general population cohort." Psychological Medicine. 43,4. 881-894. (2012 Background. The psychobiological model of personality by Cloninger and colleagues originally hypothesized that interindividual variability in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 80 publications
0
22
1
1
Order By: Relevance
“…In the present study, only the SD scores of the non-responders significantly changed based on repeated-measures two-way ANOVAs, but in the responders and early responders, the mean HA score decreased, and the mean SD score increased after the treatment. Cloninger (1987) claimed that the HA dimension correlated to serotonin, but Tuominen et al (2013) reported that there was no association between the HA dimension and the serotonin transporter density based on a positron emission tomography study; there were no significant differences in the HA dimension even though the participants took SSRIs, which influence the serotonin pathway. As such, the results of the present study support the results of Tuominen et al We could possibly follow the response to treatment for patients with MDD by investigating the SD score.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only the SD scores of the non-responders significantly changed based on repeated-measures two-way ANOVAs, but in the responders and early responders, the mean HA score decreased, and the mean SD score increased after the treatment. Cloninger (1987) claimed that the HA dimension correlated to serotonin, but Tuominen et al (2013) reported that there was no association between the HA dimension and the serotonin transporter density based on a positron emission tomography study; there were no significant differences in the HA dimension even though the participants took SSRIs, which influence the serotonin pathway. As such, the results of the present study support the results of Tuominen et al We could possibly follow the response to treatment for patients with MDD by investigating the SD score.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the findings from the current study, another study found no significant association between 5‐HT 1A R and trait Self‐transcendence (Karlsson, Hirvonen, Salminen, & Hietala, ), and two other studies reported nonsignificant associations between trait Openness and 5‐HT 4 R (Stenbaek et al, ) and 5‐HT 1A R (Tauscher et al, ), respectively. Some studies reported significant associations between 5‐HT receptor or 5‐HTT binding and other personality traits from NEO PI‐R and TCI, but none in relation to trait Openness or Self‐transcendence (Tauscher et al, ; Tuominen et al, ; Tuominen et al, ). Conversely, other PET studies investigated associations between 5‐HT receptor or 5‐HTT binding and personality traits from NEO PI‐R and TCI, but did not report associations with trait Openness or Self‐transcendence (Frokjaer et al, ; Frokjaer et al, ; Gerretsen et al, ; Moresco et al, ; Reimold et al, ; Soloff, Chiappetta, Mason, Becker, & Price, ; Soloff, Price, Mason, Becker, & Meltzer, ; Takano et al, ), possibly reflecting null findings.…”
Section: Discussionmentioning
confidence: 99%
“…A series of molecular positron emission tomography (PET) imaging studies examined the relationship between in vivo serotonergic markers and self-transcendence in groups of healthy individuals, but found inconclusive results (Borg, Andrée, Soderstrom, & Farde, 2003;Karlsson, Hirvonen, Salminen, & Hietala, 2011;Kim et al, 2015;Tuominen et al, 2013). However, the relationship between in vivo dopaminergic neurotransmission and the self-transcendence trait is hitherto undocumented.…”
Section: Introductionmentioning
confidence: 99%